Civil Servant’s E-Government Adoption Levels: Are age and context matters? - Iman Sudirman; Atya Nur Aisha; Joe Monang; Ilham Reza Prasetyo (IAES Indonesia Section, 2019)
This study examines the differences of e-government adoption by civil servants among age groups and between mandatory and voluntary context using UTAUT model. It used a non-probability sampling technique and an online survey to collect the data. A one-way ANOVA using SPSS was conducted to analyze the data. The study finds that most employees have the highest positive adoption levels in effort expectancy. Furthermore, there are significant mean differences between employee’s age group of performance expectancy for mandatory system and facilitating conditions for voluntary system. However, there is no statistically different on civil servant’s adoption level between mandatory and voluntary context.